UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PEMBELAJARAN TEMATIK SISWA MELALUI MODEL PICTURE AND PICTURE - Gustarina, Evita (ATTA`DIB, 2015)
The aim of the research is to know a thematic learning using picture and picture models can improve learning activities. This research applied classroom activities research (PTK) which conducted; planning, actuating, observation and reflection. The research found that thematic learning using picture and picture models can improve learning activities in class III B SD IT Generasi Rabbani Bengkul. This is found from the increase in average achieved scores on the activities of teachers and students that the teachers have obtained a score of 31.25 in both categories in the first cycle, increased to 36 with both categories in the second cycle, as well as the activities of the students gained an average score of 31 with either category in the first cycle, increased to 35.5 in both categories in the second cycle. It can be seen from the average value of learning outcomes and student learning in the form of a percentage of the value of cognitive (IPA 8,66 or 100%, Math 7,92 or 81,49 %), both affective and psychomotor value is 88,88 %.